The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.prostaglandins.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 modulation of blood pressure homeostasis: Studies in rodent models

Abstract: Hypertension is a well established risk factor for cardiovascular diseases such as stroke and is the leading cause of chronic kidney failure. Although a number of pharmacologic agents are available for the treatment of hypertension including agents that affect the renin-angiotensin-aldosterone system (RAAS), unmet needs in the treatment of hypertension suggest that identification of novel pharmacological targets would be an important healthcare goal. One potential target is prostaglandin E2 (PGE2), a potent li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…HWESASXX (a peptide linked to inflammation and positively associated with blood pressure) (38), and 2 eicosanoids (prostaglandin E 2 and leukotriene B 4 ) decreased with sodium restriction. Eicosanoids are known to play a role in the regulation of blood pressure (39).…”
Section: Discussionmentioning
confidence: 99%
“…HWESASXX (a peptide linked to inflammation and positively associated with blood pressure) (38), and 2 eicosanoids (prostaglandin E 2 and leukotriene B 4 ) decreased with sodium restriction. Eicosanoids are known to play a role in the regulation of blood pressure (39).…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 regulates vascular tone through activation of its four G-protein coupled receptors, EP1-EP4 (reviewed in (Swan and Breyer, 2011)). Studies in ex vivo preparations and in vivo have shown that the Gαs-coupled EP2 and EP4 receptors are vasodilatory, whereas the Gαq-coupled EP1 and Gαi-coupled EP3 receptor promote vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin E 2 (PGE 2 ) mediates pain and inflammation and has been implicated in the regulation of blood pressure 1 , thrombosis 2, 3 and atherogenesis 4 . It is generated from a prostaglandin (PG) substrate, PGH 2 , itself formed by the metabolism of arachidonic acid by PGG/H synthase enzymes, commonly known as cyclooxygenases (COXs).…”
Section: Introductionmentioning
confidence: 99%